“I Am the One That Needs Help”: The Theory of Help-Seeking Behavior for Survivors of Intimate Partner Violence - Waller, Bernadine Y. (Journal of interpersonal violence, 2023)
African American women survivors of intimate partner violence disproportionately experience homicide due, in part, to the racism and racial discrimination they experience during their help-seeking process. Yet, existing scholarship neglects to examine how this multiply-marginalized population of women navigate sociocultural barriers to obtain crisis services and supports from the domestic violence service provision system. Fundamental to developing culturally-salient interventions is more fully understanding their help-seeking behavior. We conducted 30 in-depth, semi-structured interviews with women who self-identified as African American. Constructivist grounded theory methodology was employed. Sensitizing concepts from the Transtheoretical Model of Change and Intersectionality theories, along with Agency framework were conceptually bound. The Theory of Help-Seeking Behavior emerged from the data. This nascent theory provides practitioners and researchers with a theoretical model to examine African American women’s nuanced help-seeking efforts.